Enhancing the Quality of Patchouli Oil using Zeolite and Bentonite Nano-Particle Adsorbents - Suraiya Kamaruzzaman; Syaifullah Muhammad; Sri Aprilia; Rahmat Alfano; Muhammad Ridha; Yanna Syamsuddin; Hesti Meilina (Jurnal Kimia Sains dan Aplikasi, 2021)
The overall quality of patchouli oil is closely related to the purification process during manufacturing. This research provided an effective and efficient method for purifying Aceh patchouli oil to secure high-quality patchouli oil. Purification was done by utilizing natural mineral sources that were sufficiently available in Aceh and applying them in various adsorption processes, analyzing the adsorption of Fe levels in patchouli oil, and characterizing nano adsorbents used in the adsorption process. Nanoparticles of zeolite and bentonite were used during the adsorption process with patchouli oil sourced from the South Aceh area. The adsorption process purified 20 mL of patchouli oil at a temperature of 45 ℃ with variable mass nano adsorbent 1; 3; 5 g, and variable stirring time 60; 180; 300 minutes. The purification filtrate was later analyzed for patchouli alcohol levels using Gas Chromatography-Mass Spectrometry (GC-MS) and Fe levels using UV-Vis Spectrophotometry. The characterization of nano adsorbents was conducted using Scanning Electron Microscopy (SEM) and X-ray Diffractometry (XRD). The results showed that the most efficient adsorption process occurred in nano zeolite with a mass of 5 g and a stirring time of 300 minutes, where the patchouli alcohol content was 28.54%, Fe 0.8165 mg/kg. Meanwhile, nano zeolite’s most significant constituent components were silicon oxide (SiO2) of 48.9% and silicon carbide (CSi) of 31.3%. Visually the sample did not change color due to the low quality of patchouli oil, but the Fe level in the patchouli oil samples complied with SNI 06-2385-2006 with a maximum of 25 mg/kg. In addition, nano zeolite had an adsorption capacity of 0.96 mg/g with an adsorption efficiency of 98.49%.